STUDY OF KNOWLEDGE AND ATTITUDE OF HEALTH STUDENTS ABOUT PHARMACOGENOMICS - Gamayanti, Tasiana Gisela; Rizkifani, Shoma; Untari, Eka Kartika (Jurnal Mahasiswa Farmasi Fakultas Kedokteran UNTAN, 2019)
Pharmacogenomic studies in the field of pharmacy have a role in personalized medicine so they can guarantee the delivery of drugs with the correct dose, type, indication, time, and patient. Limited information about pharmacogenomics can affect the knowledge and attitude of health students. The knowledge that a personhas can influence their attitude. The purpose of this study was to analyze the relationship between knowledge andattitude of health students towards Pharmacogenomics. Methods: This research method is an observational analysis. The sampling technique used was quota sampling by distributing questionnaires or a google form to health students at the Faculty of Medicine, University of Tanjungpura. Data analysis was performed using the ChiSquare test at confidence level of 95%. Results: Based on the responses of 360 participants (involving medical, pharmacy, and nursing study programs) at The Faculty of Medicine, University of Tanjungpura, the most frequency of participants' age was the range 19-20 years (53.33%) with the gender of female (77.50%) and male (22.50%), it was found that the level of knowledge was the best (8,89%), very good (26,39%), good (44,44%), quite good (17,50%), and not good (2,78%). The level of participants' attitude of the role of pharmacogenomics are those who have positive attitude (77,78%) and negative attitude (22,22%). Conclusions: With the highest frequency of participant characteristics are 53% at the age of 19-20 years and 77% female, it can be concluded that the health students of the Faculty of Medicine, University of Tanjungpura had a good level of knowledge and a positive attitude about pharmacogenomics.